Kajian Keselamatan Peroses Bongkar Muat Barang Yang Menimbulkan Cacat Produk Muatan Di Pelabuhan Paotere - Adriani Phady; Taufiqur Rachman; Chairul Paotonan (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
This article discusses the worker's safety assessment of the loading and unloading process that causes cargo product defects at Paotere Harbour. Makassar, which is the capital of South Sulawesi province, is known as the city with the largest majority population and is a dense flow of inter-island freight traffic. One of the Harbours that transportation the economy in Makassar is the Harbour of Paotere which provides dock services for fishing boats, passenger ships and cargo ships. Phinisi motor sailing ships are equipped with lifting equipment, namely cranes that can lift goods to facilitate the loading and unloading process of goods from the ship to the edge of the pier. However, the loading and unloading process ignores the safety and health aspects of work on the deck of the ship and on the dock. In addition, the results of the products being trans Harboured must also be considered if someone experiences product defects due to loading and unloading activities at the Harbour of Paotere. J-hook, a tool used to lift and move the sack by stabbing it in any place, can cause the sack to tear and the grain inside will slowly spill out due to gaps in the sack. The method used in this research is the descriptive method, namely: providing an overview of certain phenomena or certain aspects of the location under study. Descriptive methods are not only limited to data collection but include direct observation and interviews with workers. The strategic solution needed is the replacement of the cargo lift knot rope on the crane with a mooring rope net that facilitates the lifting process from the ship's deck to the Paotere Harbor pier. Replacing the J-hook whose function is to shift and flip the sack with an enlarged Jar Lifter tool and an adjustment of the material that is comfortable to hold and is not dangerous if it falls and hits the limbs of workers who are carrying out loading and unloading activities Paotere Harbor.